Relationship among Smoking Addiction, Psychological Flexibility, and Impulsivity in University Students - Söğütlü, Lütfiye; Göktaş, Seyyide Şifa (Addicta: The Turkish Journal on Addictions, 2021)
In this study, we aimed to investigate the relationship between psychological flexibility and impulsivity levels with nicotine addiction levels, in university students who are addicted to cigarettes. The population of the study consisted of 546 undergraduate students, including 294 non-smokers and 252 smokers, who were addicted to tobacco according to the Diagnostic and Statistical Manual of Mental Disorders 5th edition (DSM-5) diagnostic criteria and who were studying at the Hamidiye Health Sciences University. The Psychological Flexibility Scale (PFS) and Barratt Impulsivity Scale (BIS) were applied to students who were smokers and non-smokers; and in addition, the Fagerström Nicotine Dependence Test (FNDT) was applied to the smokers. The students with nicotine dependence were compared with the non-addicted group; and values (32.4±8.0 vs. 54.5±11.3; p